Slag corrosion of alumina-magnesia-carbon refractory bricks: Experimental data and thermodynamic simulation. Issue 5 (1st April 2017) - Muñoz, Vanesa; Camelli, Silvia; Tomba Martinez, Analía G.
Abstract: Alumina-magnesia-carbon (AMC) bricks are used in steelmaking ladles, where they are part of the bottom and sidewalls working linings. These refractories can be corroded by liquid slag, especially during tapping and casting. In order to contribute with information regarding the reaction mechanisms and the formed phases when they are in contact with a molten slag, the slag corrosion at high temperatures of three AMC refractories is analyzed in this paper. A crucible test was performed at 1600 °C using an industrial basic slag, and the results were compared with those obtained in testing at 1450 °C. In addition, thermodynamic simulations of the slag-refractory contact were performed using FactSage software and a model which considers the global chemical composition of each refractory. Differences in the materials wear associated with differences in composition were predicted by the simulation. Other determining factors, such as microstructure and texture of the evaluated AMC refractories, were also discussed.